Central African Economic and Monetary Community (CEMAC) : Selected Issues. (IMF Staff Country Reports; Country Report, 2015)
This Selected Issues paper compares the growth performance of Central African Economic and Monetary Community (CEMAC) countries with that of comparative countries. During the last two decades, the average growth of CEMAC countries has been slower than the sub-Saharan African average. The results of the analysis show that convergence of CEMAC countries toward emerging market levels has stalled, while some lower-income, faster-growing economies have been catching up. Decomposing growth by contributing factors reveals that the total factor productivity has had a negative impact on CEMAC's growth.